Protein Hydrolysis from Catfish Prepared by Papain Enzyme and Antioxidant Activity of Hydrolyzate - Ace Baehaki; Shanti Dwita Lestari; Achmad Rizky Romadhoni (Jurnal Pengolahan Hasil Perikanan Indonesia, 2015)
The objective of this research was to make a protein hydrolysates from catfish(Pangasius pangasius) enzymatically using papain enzyme and analyzed the antioxidant activityof protein hydrolysates produced. The research used the method completely randomized designwith two replications the treatment were the difference concentration of the papain enzyme(0%, 1%, 2%, 3%, 4%, 5%, and 6%). The parameters of research were antioxidative activity usingDPPH (2,2-difenil-1–pikrilhidrazil), protein content, and molecular weight using SDS-PAGE(Sodium Dodecyl Sulfate Polyacrylamide Gel Electrophoresis). The results showed that catfishprotein hydrolysates prepared by papain enzyme has antioxidative activity. The highest degree ofhydrolysis was 71.98% at enzyme concentration of 6%. Based on the DPPH scavenging methodcatfish protein hydrolysates has the antioxidative activity with the value 37.85-67.62%. The proteincontent of catfish protein hydrolysates were 20.86-54.47 mg/ml. The molecular weight of catfishprotein hydrolyzates were 11.90-65.20 kDa.Keywords: Antioxidant, catfish, papain enzyme, protein hydrolyzate